1974
DOI: 10.1002/eji.1830040702
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent responsiveness to branched polysaccharides and their dinitrophenyl conjugates in the Biozzi high and low responder lines of mice

Abstract: and low responder lines of mice biology, Wellcome Research Laboratories, BeckenhamDose response curves for two thymus-independent branched polysaccharides, levan and dextran B 1355, have been compared by direct plaque-forming cell assays in the Biozzi high (Ab/H) and low (Ab/L) responder lines of mice.In contrast with all of many other antigens so far tested, equivalent IgM responses were elicited by native levan (mol. wt. 2 x lo7), Pseudomonas levanicum vaccine and native dextran (mol. wt. 4 x lo7). Partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Thus, the different antigen handling by M@ from the two lines could reflect hyperactivity of L M@ in intracellular digestion resulting in a lower amount of membrane-bound antigen in immunogenic form. This view is supported by the observation that levan, which induces similar antibody responses in H and L mice [6], shows an equivalent degree of intracellular digestion in both lines [15].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, the different antigen handling by M@ from the two lines could reflect hyperactivity of L M@ in intracellular digestion resulting in a lower amount of membrane-bound antigen in immunogenic form. This view is supported by the observation that levan, which induces similar antibody responses in H and L mice [6], shows an equivalent degree of intracellular digestion in both lines [15].…”
Section: Discussionmentioning
confidence: 56%
“…Although H and L mice have not been found to differ in the in vivo phagocytosis of colloidal carbon or SRBC [14], other immunogens are phagocytosed more rapidly in L than in H mice. This is true not only for antigens which induce different antibody responses in H and L mice, such as keyhole limpet hemocyanin (KLH) and type 3 pneumococcal polysaccharide, but also for antigens, such as levan and dextran, which induce similar antibody responses in the two lines [6,151. These results imply that the rate of antigen phagocytosis is not a major factor in the regulation of antibody responsiveness in H and L mice.…”
Section: Discussionmentioning
confidence: 95%
“…These findings indicate that selective breeding has modified the general antibody synthesis, independent of antibody specificity. Nevertheless, similar responsiveness of HL and LL responders to two thymus-independent antigens, levan and dextran, has been reported [27].…”
Section: Introductionmentioning
confidence: 75%
“…These mice also differed in antibody response to a variety of other im munogens, including parasite antigens [3,14]. However, no significant differences were found between HL and LL mice with respect to their antibody formation to thy mus-independent branched polysaccharide antigens [8], Furthermore, both lines were able to develop similar delayed hypersensi tivity reactions [2]. It has been suggested that the primary factor responsible for the difference in antibody production is the di vergence in antigen handling at the level of the macrophage [21].…”
Section: Introductionmentioning
confidence: 99%